2022
DOI: 10.1111/jocn.16367
|View full text |Cite
|
Sign up to set email alerts
|

Managing Parkinson’s during the COVID‐19 pandemic: Perspectives from people living with Parkinson’s and health professionals

Abstract: Objectives:The aim of this study was to understand how people living with Parkinson's and healthcare professionals perceived their care management and interactions with health services were affected during the COVID-19 pandemic.Background: During the COVID-19 pandemic, many governments introduced restrictions and services that support Parkinson's care management had to cease or be delivered remotely. These changes may have had an impact on the well-being of people living with Parkinson's. Methods:A qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…It has been shown that over a third of people with PD (PwP; 36.3%, n = 45) taking three or more doses of medication daily report poor adherence ( 6 ). Modification of complex medication regimens often follows short, infrequent appointments with a clinician, which have been especially affected by the COVID-19 pandemic ( 7 , 8 ). In addition, patient-clinician interactions are influenced by patient recall and performance bias, and clinicians observe PwP at different stages (“ON,” “OFF” periods) of their medication regimen.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that over a third of people with PD (PwP; 36.3%, n = 45) taking three or more doses of medication daily report poor adherence ( 6 ). Modification of complex medication regimens often follows short, infrequent appointments with a clinician, which have been especially affected by the COVID-19 pandemic ( 7 , 8 ). In addition, patient-clinician interactions are influenced by patient recall and performance bias, and clinicians observe PwP at different stages (“ON,” “OFF” periods) of their medication regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Such research may be especially important for groups of people who felt vulnerable and isolated as a result of the pandemic. (Schaefer et al, 2020; Soilemezi et al, 2022; Subramanian et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on social isolation came from COVID-19 research, showing the isolation and disruption of social networks and usual activities in PD during the COVID-19 pandemic 32–34. Few studies have examined social isolation or similar constructs before the COVID-19 era 30.…”
Section: Discussionmentioning
confidence: 99%